Model-based drilling fluid flow rate estimation using Venturi flume. Issue 6 (2015) - Berg, C.; Malagalage, A.; Agu, C.E.; Kaasa, G.-O.; Vaagsaether, K.; Lie, B.
Abstract: Monitoring the flow rate out of the well is critical for good control of the downhole pressure in drilling operations. In this feasibility study, we explore the possibility of using a Venturi flume to provide a cost-effective measurement of the flow rate, with improved accuracy compared to conventional methods. A Venturi flume has been simulated both using CFD and a simplified 1D model. By proper design of the Venturi flume, a jump in the fluid level in the throat section of the flume can be injected. Four methods of using this jump information are discussed, each with their own advantages and disadvantages, such as dependence on fluid properties, length of the flume, computation time, etc. Further work is necessary to improve sensor set-up and numeric methods, as well as testing out the concepts on a Venturi rig.